Gestión de talento humano y desempeño laboral en la Municipalidad Provincial de Requena, año 2023 - Ihuaraqui Huayunga, Suelen Iris (2024)
The objective of this research was to determine the relationship between human talent management and labor performance in the provincial municipality of Requena, year 2023. The research methodology integrated a correlational and non-experimental design, quantitative approach, probabilistic sampling, a population and sample composed of 57 and 50 participants, correlatively, among workers of the Provincial Municipality of Requena and independent experts on human talent management and work performance. The main results showed the relevance of human talent management in the provincial municipality of Requena based on components such as knowledge, motivation, ability and skills of its workers, so as to have the greatest significant impact on their job performance in the institution. Finally, the main conclusion was to have determined that there is a significant relationship between human talent management and job performance in the provincial municipality of Requena, year 2023. This conclusion was compatible with the Spearman Correlation index of 0.991 for the case of the general hypothesis.